A Qualitative Study on Post Pandemic Mental Health of Private University Students in Klang Valley - Mahdi B. Hussain, Mohd Al; Jegatheswaran, Lavanyaa; Mohamed, Harnani (International Journal of Academic Research in Progressive Education and Development, 2023)
This qualitative study intends to investigate the post-pandemic mental health experiences of students at private universities in Malaysia's Klang Valley. The study involved ten respondents from five universities in the Klang Valley area with semi-structured interviews were conducted to obtain the data. The study's goals are to determine the factors that affected students at private universities' mental health after the COVID-19 pandemic, to investigate the experience of private university students' mental health, and to determine the significance of mental health support provided by private universities. The findings showed that positive factors had influenced their mental health which included: more quality time with family, the ability to multitask and the fact that they were able to avoid excessive socializing. In addition, restriction caused by the Movement Controlled order along with the transition of physical classes to online classes, the rising number of Covid-19 cases and other conflicts. They had more productive experiences that they had post the pandemic and negative such as anxious and insecure experiences and highly stressful experiences. According to respondents all of them agreed that the support of private university is very important to their post pandemic mental wellbeing.